Pengaruh Store Image Dan Store Atmosphere Terhadap Impulse Buying Pada Konsumen Dafinna Swalayan Di Tenggarong - Wahyuni, Sri; Raharjo, Sugeng (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:The main purpose of this research is to find out the influence of store image and store atmosphereon impulse buying on consumer self-service dafinna in Tenggarong. In this study used multipe regression analysis with equation model. The process of calculating data using manual tools and the distribution of questionnaires.Based onresult of f test it can be concluded that store image and store atmosphere variabels simultan eously have an effect on impulse buying. By using method entered, jika f arithmetic is bigger than f tabel (f count 80,349> f tabel 0,274). Then independent variables have a significantÂ  relationship or impulse buying variables influenced by the variable store image and store atmosphere significantly influence the impulse buying on self-service Dafinna Swalayan in Tenggarong.â€ Accepted and proven to be true.From the results of partial correlation test seen the value of the largest image store variable than the variable store atmosphere t tabel (T arithmetic 8,964< T table 1,666) So ho rejected and H1 accepted. From the results of the partial test looks the most dominant influence on impulse buying on Dafinna Swalayan in Tenggarong.â€ Accepted and proven to be true.Keywords : Store Image, Store Atmosphere, Impulse Buying